An examination of Illinois free banks: Bank ownership, operations, and free bank failures - Andrew James Economopoulos (Essays in Economic & Business History (EEBH), 2021)
This article re-examines Illinois free banking from a new perspective: ownership structure. The claim that ownership influenced banking activity and noteholder losses is analyzed, and it is shown that ownership did not have a major impact on asset allocation and losses. Only Chicago residents who owned banks elsewhere appear to have used the banks for their interests. They neither issued loans to borrowers other than themselves or accepted deposits. Private bankers used free banks as a source of banknotes. A large proportion of the free banks had overlapping ownership, resulting in specie minimization. Private bankers, whether local or from Chicago, and local owners were more likely to operate as traditional banks. All free banks were impacted by the 1853 change in the tax code, leading to fewer loans, more loans to stockholders, and more deposits in other banks. Free banks owned by Chicago private bankers generally closed without noteholders suffering losses. For closed banks owned by other ownership groups noteholder losses depended on the nature of the bonds held by the bank.
Keywords: N2; 330; Free Banking; Bank Ownership; Bank Failures; Private Bankers; Illinois